Effect of different polishing methods on surface roughness of provisional prosthetic materials - Ivian Verena Maia Tupinamba; Priscila Couy Corrêa Giampá; Isadora Almeida Rios Rocha; Emilena Maria Castor Xisto Lima (Wolters Kluwer Medknow Publications, 2018)
Purpose: To evaluate the surface roughness of bis-acrylic and acrylic resins submitted to different methods of polishing. Materials and Methods: Fifty samples of each provisional restorative material (Structur 2, Protemp 4, Duralay, and Dencrilay) were fabricated (10 mm × 2 mm) and divided into five groups (n = 10): (1) positive control group - polyester strip; (2) negative control - unpolished; (3) abrasive tips (Exa-Technique-Edenta); (4) goat hair brush and diamond polishing paste; and (5) silicone tips (Enhance). Each material was mixed and polymerized according to manufacturer's instructions. The parameter evaluated was the arithmetic mean of the surface roughness (Ra) determined using the rugosimeter SJ 301 (Mitutoyo, Japan). The data were analyzed with two-way analysis of variance (post hoc Tukey's test) (P < 0.05). Results: The lowest surface roughness values (0,22-0,90 μm) were observed in the Group 4 - goat hair brush and diamond paste, while the highest values (1,17-1,44 μm) were found in the Group 5 - silicone tips (enhance), with statistically significant differences between them, except for Dencrilay acrylic resin. There was statistically significant difference between bis-acrylic and acrylic resins in the Groups 1, 2, and 4. Conclusions: Within the limitations of this study, it was concluded that the most effective polishing system was the goat hair brush with diamond paste for both bis-acrylic and acrylic resins. The bis-acrylic resins exhibited significantly smoother surfaces than the acrylic resins.